2004
DOI: 10.1192/bjp.185.2.152
|View full text |Cite
|
Sign up to set email alerts
|

Testing for diabetes in hospitalised patients prescribed antipsychotic drugs

Abstract: Testing for diabetes was undertaken in less than half of the patients studied. Testing was more common in those receiving atypical antipsychotics. Apparent differences in claimed causal association of the use of some antipsychotics with diabetes may in part reflect different rates of testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 19 publications
3
45
0
2
Order By: Relevance
“…This concurs with the results of previous studies (Gul et al, 2006;Mackin et al, 2007;Motsinger et al, 2006;Taylor et al, 2004).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This concurs with the results of previous studies (Gul et al, 2006;Mackin et al, 2007;Motsinger et al, 2006;Taylor et al, 2004).…”
Section: Discussionsupporting
confidence: 83%
“…However, many studies found that monitoring was still poor (Motsinger et al, 2006;Taylor et al, 2004). A prospective cohort study in Northeast England that studied 83 subjects on antipsychotics revealed that none of them were monitored for their BMI and waist circumference.…”
Section: Introductionmentioning
confidence: 99%
“…All patients were taking atypical antipsychotic medication, but this association was not statistically significant. The prevalence of undiagnosed glycaemic disorder here is similar to that reported in a recent study in which case notes from hospitalised patients prescribed antipsychotic drugs were examined for evidence of testing for diabetes [25]. The study by Taylor et al reported a prevalence of glucose homeostasis disorder of 15.6% in those tested, and no association between the prevalence of hyperglycaemia and the type of antipsychotic medication was found.…”
Section: Discussionsupporting
confidence: 71%
“…Screening for diabetes varies between different agents, with patients receiving second-generation antipsychotics being much more likely to be screened than those receiving 'typical' drugs [9,10]. This is important because as many as 70% of cases of diabetes in patients with schizophrenia are undiagnosed, and only through a systematic screening programme will all new cases of diabetes be identified [11].…”
Section: The Sources Of Evidence Linking Antipsychotic Drugs and Diabmentioning
confidence: 99%
“…An alternative explanation may be that the rate of diabetes in patients with SMI is increasing in line with the general population and any further increase reflects an increased awareness of the need to screen for diabetes in patients with SMI [9].…”
Section: Plausibilitymentioning
confidence: 99%